A CONCEPTUAL MODEL FOR IFC-BASED DELINEATION OF CONDOMINIUM RIGHTS IN TURKEY: INITIAL EXPERIMENTS - D. Guler; T. Yomralioglu (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2021)
Owing to the increasing existence of multistorey buildings and infrastructures in the built environment, there is a need for three-dimensional (3D) land administration systems (LAS). Regarding this, condominium rights in real-estate properties are needed to be represented as 3D for preventing misinterpretations with regards to who is responsible for or has ownership in which parts of the buildings. Digitalizing the public services appears in current strategies of governments and administrations since it contributes to transparency, speed, and accurateness in the processes. Building permitting that contains obtaining the occupancy permit is a vital one of these public services. With the even-increasing adaptation of Building Information Modelling (BIM), a whole raft of Building Information Models (BIMs) are created to use in digital building permitting. Thus, a significant opportunity for 3D delineation of condominium rights comes out of the reuse of these BIMs, especially their Industry Foundation Classes (IFC) data. In this sense, this paper puts forward an approach that includes developing the conceptual model to depict condominium rights and linking that model with the IFC schema. The applicability of the approach is demonstrated by using a floor of a simple building. The study shows that IFC-based representation of condominium rights can be beneficial for the transition to 3D LAS in Turkey.